Pioneering Informed Consent for Return of Research Results to Breast Cancer Patients Facing Barriers to Implementation of Genomic Medicine: The Kenyan BRCA1/2 Testing Experience Using Whole Exome Sequencing - Torrorey-Sawe, Rispah; van der Merwe, Nicole; Mining, Simeon Kipkoech; Kotze, Maritha J. (Frontiers in Genetics, 2020)
Abstract Introduction: Obtaining informed consent from study participants and disseminating the findings responsibly is a key principle required for ethically conducted clinical and genetic research. Reports from African researchers providing feedback on insights gained during return of whole exome sequencing results to study participants in resource-limited settings is lacking. Aim: The empirical process used to fill this gap in relation to BRCA1/2 mutation screening provided unique insights incorporated into a pathology-supported genetic testing algorithm for return of research results to Kenyan breast cancer patients. Methods: The Inform consent form approved by the Moi Teaching and Referral Hospital in Kenya was adopted from a translational research study conducted in South Africa. Initially, the informed consent process was piloted in 16 Kenyan female patients referred for breast surgery, following a community-based awareness campaign. A total of 95 female and two male breast cancer patients were enrolled in the study from 2013-2016. Immunohistochemistry (IHC) results of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) status were obtained from hospital records. DNA of patients with a family history of cancer was extracted from saliva and sequenced to screen for pathogenic mutations in the BRCA1/2 genes. Results: Ten patients approached for participation in this study declined to sign the informed consent form. Data on IHC used as a proxy for molecular subtype were available in 8 of 13 breast cancer patients (62%) with a family history of cancer. Five BRCA1/2 variants of uncertain clinical significance were detected, as well as a pathogenic BRCA2 mutation (c.5159C>A; S1720*) in a female patient eligible for return of research results. Conclusion: Experience gained during the qualitative pilot phase was essential to overcome challenges associated with the translation of sophisticated genetic terms into native African languages. Detection of a BRCA2 mutation in a patient with familial breast cancer, frequently associated with hormone-positive breast carcinoma as reported in this case, led to a high level of confidence on which to base risk management in future. Implementation of new technologies alongside standard pathology provides a practical approach to the application of genomic medicine in Africa.